SISTEM FUNDRAISING ZAKATLEMBAGA PEMERINTAH DAN SWASTA (Studi Komparatif pada Badan Amil Zakat Nasional (BAZNAS) Kota Palu dan Pos Keadilan Peduli Umat (PKPU) Palu Periode 2010-2014) - Uswatun Hasanah (ISTIQRA, 2015)
Fundraising can be defined as activities in order to collect funds from the public and other resources of the society (individual, group, organization, company, or government) that is used to fund programs and operational activities of the organization / institution to achieve its objectives. In order for operational activities and programs at the Zakat institution can be continued, the fundraising activity absolutely must be done properly and strategically. Zakat Institutions business success depends on the seriousness in carrying out fundraising activities. This article discusses the system of fundraising zakat in the National Zakat Agency (BAZNAS) Palu and Pos Keadilan Peduli Umat (PKPU) Palu